-(-7y+3z-9)=

Simple and best practice solution for -(-7y+3z-9)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(-7y+3z-9)= equation:


Simplifying
-1(-7y + 3z + -9) = 0

Reorder the terms:
-1(-9 + -7y + 3z) = 0
(-9 * -1 + -7y * -1 + 3z * -1) = 0
(9 + 7y + -3z) = 0

Solving
9 + 7y + -3z = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + 7y + -9 + -3z = 0 + -9

Reorder the terms:
9 + -9 + 7y + -3z = 0 + -9

Combine like terms: 9 + -9 = 0
0 + 7y + -3z = 0 + -9
7y + -3z = 0 + -9

Combine like terms: 0 + -9 = -9
7y + -3z = -9

Add '3z' to each side of the equation.
7y + -3z + 3z = -9 + 3z

Combine like terms: -3z + 3z = 0
7y + 0 = -9 + 3z
7y = -9 + 3z

Divide each side by '7'.
y = -1.285714286 + 0.4285714286z

Simplifying
y = -1.285714286 + 0.4285714286z

See similar equations:

| 2w^4-9w^2+4=0 | | (1/2)^lgx1 | | 19.75-7.19+0.50= | | (z^2+1)(-2z^2+3z-2)=0 | | 10x+9=3(3x+6) | | =12+2 | | 3x+y-2z=9 | | 65=6x+7y | | 1.4+0.3=1.7 | | -4(5y-5)-y=-2(y-4) | | .7x-1.5=.4x+1.2 | | 6(r+7)=60 | | 5/9=x-1/12 | | 2x-4(x-2)=-4+5x-23 | | ln(x-7)=ln(x+5) | | 16x(5-x)=30 | | x-x^2=56 | | -9=-11+6 | | 67=11+7x | | 26+6s=74 | | -3(x+2)-4=-1 | | (14+a)+14= | | -2z+-4=6 | | 14x-12=36+x^2 | | -3(2y-3)-y=-2(y-3) | | 10+(3+b)= | | 8x-4x+3=8 | | 3z/7-7=4 | | -37=8x+3 | | 6=-2r-2 | | 6.5x=24 | | 17*(ab)= |

Equations solver categories